Proceedings of the 1st International Conference on Social Sciences Education - "Multicultural Transformation in Education, Soci 2018
DOI: 10.2991/icsse-17.2018.36
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English in Multiethnic Classroom: A Case Study on Phonemic Variation of Secondary School Students in Central Kalimantan

Abstract: Abstract-Teaching English in multicultural or in multiethnic situation presents a unique challenge as the question is often raised by English teachers as to which variety of English phonemes or pronunciation should be accurately accepted. Indonesia has approximately 757 languages to be spoken by the same number of ethnic groups. Multicultural education is a very challenging issue to all aspects of studies today. It also applies to linguistics, where multiethnic students bear a unique perspective in the languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…They substituted the sounds which exist in their L1, namely [d], [t] and [ʃ] for the target sound [ð] due to the L1 transfer. This is also similar to Fauzi (2018) in his study on English pronunciation where some English consonant sounds are difficult to be pronounced by certain ethnics of Indonesian learners such as and [ʧ]. The reason for them being difficult is that they are commonly unfamiliar and some of them are not found in learners' native language.…”
Section: Fricative Marked-sounds Acquired By English Learnerssupporting
confidence: 81%
“…They substituted the sounds which exist in their L1, namely [d], [t] and [ʃ] for the target sound [ð] due to the L1 transfer. This is also similar to Fauzi (2018) in his study on English pronunciation where some English consonant sounds are difficult to be pronounced by certain ethnics of Indonesian learners such as and [ʧ]. The reason for them being difficult is that they are commonly unfamiliar and some of them are not found in learners' native language.…”
Section: Fricative Marked-sounds Acquired By English Learnerssupporting
confidence: 81%
“…The difficulty level in learning another language can be directly connected to the students' first language(s) in relation to the degree of linguistic differences (Sung, 2021). In terms of phonology, when some phonetic features in the target language are not found in the first language(s), students tend to produce dissimilar sounds (Fauzi, 2018). In the same vein, Goswami (2020) also found that the errors committed by Sylheti Bangla speakers of English can be attributed to the interference of the rules of their first language in learning the second language.…”
mentioning
confidence: 99%